Aleuritin, a novel dinor-diterpenoid from the twigs of Aleurites moluccanus with an anti-lymphangiogenic effect. Issue 39 (30th September 2020) - Chang, Fang-Rong; Wang, Shih-Wei; Chen, Shu-Rong; Lee, Ching-Ying; Sheu, Jyh-Horng; Cheng, Yuan-Bin
Abstract : Two new compounds designated aleuritin (1 ) and aleuritone (2 ) with anti-lymphangiogenic activity were isolated from the twigs of Aleurites moluccanus . Abstract : A phytochemical investigation of Aleurites moluccanus yielded one novel dinor-diterpenoid, aleuritin (1 ), along with a rare diterpenoid, aleuritone (2 ). Compound 1 has an unprecedented skeleton with a 6/6/5-fused tricyclic ring system. Compound 2 possesses a rare 6/6/5/3-fused tetracyclic skeleton, which is probably an artifact formed photochemically by the Norrish reaction. The structures of 1 and 2 were determined by spectroscopic methods (ECD, IR, mass, and NMR) and confirmed by single-crystal X-ray diffraction analyses. A plausible biogenetic pathway of 1 is proposed. Pharmacological study showed that these two compounds possessed mild in vitro anti-lymphangiogenic activity, which suppressed tube formation with IC50 values of 48.1 ± 1.8 and 34.2 ± 0.8 μg mL −1, respectively.